Using ICT Facilities by Science Teachers during COVID-19 Pandemic in Higher Education - Yadav, Rajeshwer Prasad (Siddhajyoti Interdisciplinary Journal, 2024)
Several adverse educational impacts are observed due to COVID-19 pandemic in academic sessions in the Nepalese higher education system. The aim of the study was to describe the exiting situation of using of ICT tools for online teaching by science education teachers at higher level both in constituent and affiliated campuses in Madhesh Province, Nepal. The study followed descriptive research design with in quantitative framework. The population of the study were science teachers from both the constituent and affiliated campuses and by applying census sampling all 103 teachers were selected for the study. The data were collected through survey questionnaires. I analyzed data by applying Statistical Package for Social Science (SPSS) Version 20. The result shows that constitute campuses hadbetter ICT facilities than affiliated campuses but the practice was adverse. Less than one-third teachers had better practice of ICT tools for online teaching and learning. It was also found that MS Teams and Zoom were two widely used learning platforms but Zoom was more popular. Most of the science teachers had limited knowledge of ICT with poor ICT friendly culture. However, teachers’ ICT competencies significantly support for the paradigm shift towards online science teaching in Madhesh Province.